Stem Cell Research Awareness and Perception in Nigeria: Inferences from Sickle Cell Advocacy Centers in Kano and Lagos - Akon Ekpenyong Usoh; Jamiu Adeniyi Yusuf (Indonesian Journal of Health Research and Development, 2026)
Abstract Background: Sickle cell disease (SCD) remains a critical public health challenge in Nigeria, particularly in Lagos and Kano, where prevalence is high. Although hematopoietic stem cell transplantation (HSCT) is an advancing global cure, awareness and acceptance of stem cell therapies in Nigeria are alarmingly low.Aims: This study examines public knowledge and attitudes toward stem cell research and treatments in Lagos and Kano. It also explores barriers to acceptance and evaluates the role of advocacy and institutional programs in promoting awareness.Methods: A mixed-method approach was adopted. Quantitative data were collected from 400 respondents using structured questionnaires, while qualitative insights came from key informant interviews with healthcare professionals and advocacy staff. Four SCD centers were also assessed for their stem cell awareness programs.Result: Findings show that only 32.5% of Lagos respondents and 18.7% of Kano respondents had prior awareness of stem cell research, with far fewer demonstrating accurate knowledge of its applications and safety. Major barriers to acceptance include cultural beliefs, ethical concerns, financial constraints, and misinformation. Of the four centers evaluated, only one had a structured awareness program, while advocacy efforts were hindered by inadequate funding, limited technical training, and weak engagement with healthcare institutions.Conclusion: Public awareness of stem cell therapies in Nigeria is critically low. Strengthening advocacy capacity, implementing targeted education campaigns, and expanding government support through policy and financing are essential to improve access, acceptance, and utilization of novel stem cell treatments for SCD.